The making of outstanding Filipino scientists: Implications on enhancing giftedness in science - Mingoa, Thelma Rabago (Animo Repository, 2008)
This is a qualitative study of Filipino scientists' traits, attitudes, childhood experiences, school life, community life, science-related concerns for the youth, and the people and events that influenced their choice of a science career as well as their outstanding performance as scientists. The objective is to gather ideas that may be useful in designing programs for nurturing the special competence of gifted learners who are science-inclined. The sample consisted of 24 scientists across four age groups -Group I ( school age, ISEF winners), Group II (ages 25 to 35, NRCP members), Group III (ages 36 to 45, Outstanding Young Scientists) and Group IV (ages 46 and above, National Scientists and Academicians); and representing four disciplines - biology, chemistry, physics and mathematics. The Lives of the scientists were traced using ex post facto method. (1) Questionnaire survey, (2) document analysis, (3) interviews and (4) focus group discussion (FGD) were done to get a picture of what a successful scientist is, what is the nature of his work, how he got into science, what factors have influenced his choice of career, what are his frustrations and his recommendations for improving the state of science education in the Philippines. Data analysis procedure was descriptive. The findings are as follows: A typical outstanding Filipino scientist could be one of any age beyond college years, usually from the middle class, who usualy studied in the Philippines for elementary, high school and college but usually studied abroad for post-graduate studies. He/she is intelligent and has a very strong drive to succeed. He/she has very supportive parents, usually studied in good schools (not necessarily special science schools), and had highly qualified and inspiring teachers and mentors. He/she usually grew up close to nature, or has been substantialy exposed to nature and science equipment, and started to be interested in science in the early elementary years. He/she is usually religious, can work in an intra- or interdisciplinary team, and has a very strong love for the country. Among the scientists' frustrations and concerns for the youth are: unqualified teachers; huge class size; unsupportive culture; limited hands-on experience due to a very traditional curriculum in basic education; limited and inflexible scholarships; limted funds for research; and inefficiency and corruption in government provision of resources for projects in S&T. The findings point to the need for (a) a learning environment that would foster the learners' early recognition of their inclination to science, (b) programs that are designed to nurture giftedness in science, (c) collaboration among the school, home and community to provide a supportive learning environment for all, and (d) a science talent pool from which will emerge highly capable scientists, inventors and technicians, a human resource which will undertake or facilitate researches and inventions that address the country's needs today.